2012
DOI: 10.1111/1755-0998.12035
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Genetic Resources added to Molecular Ecology Resources Database 1 August 2012 – 30 September 2012

Abstract: This article documents the addition of 83 microsatellite marker loci and 96 pairs of single-nucleotide polymorphism (SNP) sequencing primers to the Molecular Ecology Resources Database. Loci were developed for the following species: Bembidion lampros, Inimicus japonicus, Lymnaea stagnalis, Panopea abbreviata, Pentadesma butyracea, Sycoscapter hirticola and Thanatephorus cucumeris (anamorph: Rhizoctonia solani). These loci were cross-tested on the following species: Pentadesma grandifolia and Pentadesma reynder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…We found evidence of LD (p < 0.001) between Pgen4_1 and Pgen4_10. A similar range of alleles (4-23 per locus) were found in the congener P. abbreviata in microsatellite loci (n = 21) obtained from NGS (Ahanchede et al, 2013) and similar results have been reported in others mollusk (An & Lee, 2012;Greenley et al, 2012). The quality of a marker can be determined by its degree of polymorphism.…”
Section: Introductionsupporting
confidence: 83%
“…We found evidence of LD (p < 0.001) between Pgen4_1 and Pgen4_10. A similar range of alleles (4-23 per locus) were found in the congener P. abbreviata in microsatellite loci (n = 21) obtained from NGS (Ahanchede et al, 2013) and similar results have been reported in others mollusk (An & Lee, 2012;Greenley et al, 2012). The quality of a marker can be determined by its degree of polymorphism.…”
Section: Introductionsupporting
confidence: 83%
“…Microsatellites specific for G. divaricata (López-Márquez et al, 2016) were initially tested using nested-PCR conditions following the protocol developed for the mollusc Panopea abbreviata and the nemertean Malacobdella arrokeana (Ahanchédé et al, 2013; Alfaya et al, 2014, respectively). This consisted in a two steps PCR: in the first round, a forward primer with a tail at its 5′ end (PaulAn, see Acevedo et al, 2009) and a reverse primer were used.…”
Section: Methodsmentioning
confidence: 99%
“…For Philotrypesis, two hundred and seven individuals were genotyped at 6 unlinked microsatellite loci (P50, P86, P91, P123, P129 and P202) that had been previously developed for the species [31], and for Sycoscapter hirticola , one hundred and fourty-eight individuals were genotyped at 7 unlinked microsatellite loci (S7, S27, S52, S122, S132, S137 and S162) that had been previously developed for the species [32]. Molecular analysis techniques followed Abellò et al [31] for P. josephi and Ahanchédé et al [32] for S. hirticola .…”
Section: Methodsmentioning
confidence: 99%
“…Molecular analysis techniques followed Abellò et al [31] for P. josephi and Ahanchédé et al [32] for S. hirticola .…”
Section: Methodsmentioning
confidence: 99%